Depreciation policy and its impact on the financial performance of production - Галахова, Оксана Валеріївна; Зайцев, Олександр Васильович (Technology audit and production reserves, 2013)
The paper gives the comparative analysis of two systems of depreciation policy inUkraine. The depreciation policy «before» and «after» the adoption of the Tax Code of Ukraine, which has been used since January 1, 2011. The analysis was carried out on the basis of the indicator — the period of full depreciation of fixed assets. The depreciation policy before the Tax Code implied very long depreciation period. For example, buildings were depreciated within the period from 60 to 120 years, and electronic means, for example, computers — from 15 years and more. These periods were not regulated by the enterprise but were the result of the calculation of depreciation. Depreciation charges were relatively small. Such policy prevented the replacement of the fixed production assets by the new, according to market requirements. After the introduction of the Tax Code, the depreciation policy has changed. Now the enterprise itself chooses the depreciation period, and, on its basis calculates the depreciation. For example, now buildings can be depreciated in the period from 20 years, and computers — from 2 years. Now the enterprises inUkrainechoose the depreciation periods themselves. The paper shows that existing in Ukraine rules of construction of the economic activity provide ample opportunities for owners and managers of the enterprises to build the depreciation processes, choose the most appropriate approach to the implementation of the depreciation policy for a specific situation, which corresponds to the activity objectives and development of the particular enterprise for each specific situation. This paper shows the attractiveness of modern depreciation policy to the enterprises in Ukraine.